Bridging Lossy and Lossless Compression by Motif Pattern Discovery - Apostolico, A.; Comin, M.; Parida, L. (General Theory of Information Transfer and Combinatorics, 2006)
We present data compression techniques hinged on the notion of a motif, interpreted here as a string of intermittently solid and wild characters that recurs more or less frequently in an input sequence or family of sequences. This notion arises originally in the analysis of sequences, particularly biomolecules, due to its multiple implications in the understanding of biological structure and function, and it has been the subject of various characterizations and study. Correspondingly, motif discovery techniques and tools have been devised. This task is made hard by the circumstance that the number of motifs identifiable in general in a sequence can be exponential in the size of that sequence. A significant gain in the direction of reducing the number of motifs is achieved through the introduction of irredundant motifs, which in intuitive terms are motifs of which the structure and list of occurrences cannot be inferred by a combination of other motifs’ occurrences. Although suboptimal, the available procedures for the extraction of some such motifs are not prohibitively expensive. Here we show that irredundant motifs can be usefully exploited in lossy compression methods based on textual substitution and suitable for signals as well as text. Actually, once the motifs in our lossy encodings are disambiguated into corresponding lossless codebooks, they still prove capable of yielding savings over popular methods in use. Preliminary experiments with these fungible strategies at the crossroads of lossless and lossy data compression show performances that improve over popular methods (i.e. GZip) by more than 20% in lossy and 10% in lossless implementations.